Det flexibla livet som journalister älskar : En jämförelse mellan journalister på en tidning och radioredaktion i norra Sverige - Hansson Vikström, Greta; Hedlund, Julia (Umeå universitet, Institutionen för kultur- och medievetenskaper, 2017)
Abstract Title: “Journalists who loves the flexible life” - A case between journalists occupational perception and work-future who works at a newspaper compared to a radio station in northern Sweden. This study is a qualitative comparison between journalists without permanent employment on a commercial newspaper and a public service owned radio station in a medium sized town in northern Sweden. The main purpose was to analyse the occupational perception and work-future among young journalists without permanent employment in the public service and the commercial sector. Another intention was to figure out if there was any similarities or differences between working for a public service owned radio station compare to a commercial newspaper. We wanted to investigate how these journalists experience and manage their work and in which way they look at their own future and journalism in general. The research applies theories such as the precariat and studies about convergence. The chosen method for the study were qualitative semi-structured interviews based on the answers from six journalists and was processed through a thematic analysis. The main conclusion of this study was that multi journalism has become a part of the journalistic agenda, both on the radio station and the newspaper. It showed that journalists has to be flexible when it comes to working schedules. Even though they had to adapt to a lot of the journalistic requirement they still accepted the funny, but yet stressful life as a journalist. One conclusion that can be drawn is that todays journalism can demand almost anything, and job seeking journalists will adapt quite well regardless of change. A final conclusion was that it's difficult to predict the future of these journalists. But a common stand point for the journalists was that almost everyone could imagine a future in another profession.